The Influence of Flash Sale And Brand Image On Purchasing Decisions (Skincare User Study the Originote on Shopee E-Commerce in Majalengka Regency) - Sopiyan, Pipih; Abdullah, Dudung; Rusdiana, Alan; Graziani, Athila (Finance and Business Management Journal, 2025)
The beauty industry in Indonesia continues to develop year by year. Many people want to improve and enhance their skin to feel confident when meeting others around them. This encourages companies to continuously develop attractive marketing strategies and retain consumers due to the emergence of many new, local skincare brands. The availability of good flash sales will facilitate consumers in purchasing these products. Another factor that drives purchasing decisions is brand image; when the brand image associated with a product is high, it makes it easier for, consumers to recognize the product, thus facilitating their purchasing decisions. This research aims to determine how flash sales and brand image affect the purchasing decisions of The, Originote skincare products on the Shopee E-Commerce platform. The method used in this study is a survey method with a descriptive and verificative approach. size of 100 respondents. Data collection techniques include questionnaires. The analytical tools used in this study are multiple linear regression analysis and the coefficient of determination analysis, which is preceded by classical assumption testing, followed by model feasibility testing and hypothesis testing (t-test).